Remembering Eden: the reception history of Genesis 3: 22-24 - Lanfer, Peter Thacher (Oxford University Press, 2012)
In this book, Peter Thacher Lanfer seeks to evaluate texts that expand and explicitly interpret the expulsion narrative of Adam and Eve in Genesis beyond the biblical canon